The Evolution of Defense Policies: Trends and Factors Shaping National Strategies - Dwi Riantoko; Eko Prasojo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study examines the evolution of defense policies in different countries and identifies the common trends and factors that have influenced their development over time. By analyzing changes in the global security landscape, advancements in military technology, the role of relationships between countries, and the driving forces of national interests, regional stability, and sovereignty protection, this research offers valuable insights into the dynamic nature of defense policies. Understanding these underlying factors is essential for comprehending the complexities of defense strategies, anticipating future challenges, and fostering effective international cooperation to address shared security concerns.